Inventarisasi Sarana dan Prasarana Pendidikan di SMPN 50 Palembang - Apriliani, Sella; Setyaningsih, Kris; Rohman, Asep (Indo-MathEdu Intellectuals Journal, 2025)
The inventory of educational facilities and infrastructure involves the systematic and orderly registration of school-owned items into the inventory system. This process is important as it helps schools identify deficiencies and surpluses in facilities. This study aims to examine the process of inventorying educational facilities and infrastructure at SMP Negeri 50 Palembang. The research employs a qualitative method with a descriptive qualitative approach, using data collection techniques such as interviews, observations, and documentation. The data analysis techniques used in this study include data reduction, data display, and data verification. Data validity was tested using source triangulation and technique triangulation. The findings show that the inventory process for facilities and infrastructure is carried out properly according to procedures, with a computerized system supporting the inventory activities at SMP Negeri 50 Palembang. However, there are some challenges in the inventory activities, such as a lack of human resources skilled in coding due to overlapping work systems and a complicated coding system, which makes data retrieval difficult